Electrochromic properties of nanostructured tungsten trioxide (hydrate) films and their applications in a complementary electrochromic device - Sun, Xiaowei (2013)
Orthorhombic hydrated tungsten trioxide (3WO3·H2O) films consisted of nanosticks and nanoparticles were prepared on fluorine doped tin oxide (FTO)-coated substrate by a facile and template-free hydrothermal method using ammonium acetate (CH3COONH4) as the capping agent. Irregular nanobrick films were obtained without capping agent. Due to the highly rough surface, the nanostick/nanoparticle film depicts faster ion intercalation/deintercalation kinetics and a greater coloration efficiency (45.5 cm2/C) than the nanobrick film. A complementary electrochromic device based on the nanostick/nanoparticle 3WO3·H2O film and Prussian blue (PB) was assembled. As a result, the complementary device shows a higher optical modulation (54% at 754 nm), a larger coloration efficiency (151.9 cm2/C) and faster switching responses with a bleaching time of 5.7 s and a coloring time of 1.3 s than a single 3WO3·H2O layer device, making it attractive for a practical application.